2011
DOI: 10.1063/1.3623434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light scattering on the transmission spectra of organic nanocrystals

Abstract: The effect of light scattering on the extinction spectra of organic nanocrystals was investigated by absorption and extinction measurement and by theoretical calculation for typical organic nanocrystals of a-perylene. In the extinction spectra, the exciton band shows a size-dependent redshift and tail toward longer wavelengths due to scattering as the crystal size is increased beyond $50 nm. In the absorption spectra, the exciton band blueshifts from that in the bulk crystal for crystal sizes less than $200 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The dynamic light scattering (DLS) experimental results showed that the average diameters of particles for different concentrations were 340 nm (1 × 10 –4 M), 375 nm (1.5 × 10 –4 M), 415 nm (2 × 10 –4 M), 463 nm (2.5 × 10 –4 M), and 601 nm (3 × 10 –4 M). For the solution systems with large size organic particles, their emission and absorption properties may be influenced by the scattering of the organic particles . The emission spectra presented in Figure S1 have been obtained based on the excitation wavelength of 500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic light scattering (DLS) experimental results showed that the average diameters of particles for different concentrations were 340 nm (1 × 10 –4 M), 375 nm (1.5 × 10 –4 M), 415 nm (2 × 10 –4 M), 463 nm (2.5 × 10 –4 M), and 601 nm (3 × 10 –4 M). For the solution systems with large size organic particles, their emission and absorption properties may be influenced by the scattering of the organic particles . The emission spectra presented in Figure S1 have been obtained based on the excitation wavelength of 500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The emission spectrum of the MCs is red-shifted relative to the emission spectrum of the perylene molecule, as expected due to the aggregation of perylene in the MCs. The emission of solid-state perylene has been well studied, and it is generally understood to be made up of emission from E-type and Y-type excimers. ,,,,, The E-type excimer is formed on the perylene sandwich dimer, while the Y-type excimer is formed in the next-nearest parallel pair of molecules. In perylene single crystal studies, the E-type excimer is observed at room temperature, whereas the Y-type excimer is only observed at low temperatures (10–30 K). , In perylene microcrystals, however, both the E- and Y- types are observed at room temperature. ,, In the observed emission spectra for the plate-, rod-, and cube-shaped perylene MCs, the peak around 575 nm is attributed to the formation of an E-type excimer, while the shoulder at 520 nm is attributed to the Y-type excimer. ,, The Y-states are populated from the optically excited monomeric singlet (S 1 state), whereas the E-states are generated by the thermally activated energy transfer from the Y-state .…”
Section: Resultsmentioning
confidence: 99%
“…Similar absorption tails have been observed in the long wavelength region of reported perylene MC spectra, and they are generally attributed to the scattering effects. 65,66 The peaks due to scattering are more prevalent in the rods because of their larger dimensions compared to those of the cubes (Figure S9). The square rods obtained in the presence of the MoD-2 showed a higher intensity of low-energy transitions (ca.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We experimentally confirmed that crystals of more than ∼100 nm in size exhibit a redshifted FE band in the extinction spectra measured by transmission geometry, with a small solid angle of observation. 20 Other weak structures, i.e., dips in Fig. 4(c) at 2.77 eV, in Fig.…”
mentioning
confidence: 90%